2020
DOI: 10.1073/pnas.1916343117
|View full text |Cite
|
Sign up to set email alerts
|

The mechanochemistry of the kinesin-2 KIF3AC heterodimer is related to strain-dependent kinetic properties of KIF3A and KIF3C

Abstract: KIF3AC is a mammalian neuron-specific kinesin-2 implicated in intracellular cargo transport. It is a heterodimer of KIF3A and KIF3C motor polypeptides which have distinct biochemical and motile properties as engineered homodimers. Single-molecule motility assays show that KIF3AC moves processively along microtubules at a rate faster than expected given the motility rates of the KIF3AA and much slower KIF3CC homodimers. To resolve the stepping kinetics of KIF3A and KIF3C motors in homo- and heterodimeri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 64 publications
(80 reference statements)
2
11
0
Order By: Relevance
“…These results are also in agreement with the work by Bensel et al. ( 22 ), where they found that fitting KIF3AC dwell time cumulative distribution data generated from interferometric scattering microscopy experiments could only be statistically justified with a single-exponential function rather than the sum of two exponentials. Moreover, their step trajectory analysis showed that alternating steps had similar step lifetimes.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These results are also in agreement with the work by Bensel et al. ( 22 ), where they found that fitting KIF3AC dwell time cumulative distribution data generated from interferometric scattering microscopy experiments could only be statistically justified with a single-exponential function rather than the sum of two exponentials. Moreover, their step trajectory analysis showed that alternating steps had similar step lifetimes.…”
Section: Discussionsupporting
confidence: 92%
“…The results presented here and those from Bensel et al. ( 22 ) indicate that KIF3AC is an unconventional processive kinesin, yet the question becomes how do these mechanochemical properties enable the physiological function of KIF3AC in neurons? Because neurons are highly polarized cells that depend on selective transport of specific vesicles to axons and dendrites ( 1 , 29 , 30 , 31 ), the first thought is that KIF3AC transports specific cargoes yet to be identified.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Second, inspired by previous work on heterogeneity in the microtubule lattice [5658], we show how motor motility changes if the lattice contains a random mixture of sites with different motor binding affinity. Third, building on previous work on heterodimeric kinesin motors [104109], we create a toy model of a heterodimeric motor in which one head is immobile while bound while the other head can diffuse while singly bound. The model demonstrates the expected crossover from directed to diffusive motility as the diffusion coefficient of the second head increases.…”
Section: Resultsmentioning
confidence: 99%